2018
DOI: 10.1183/13993003.00385-2018
|View full text |Cite
|
Sign up to set email alerts
|

Familial aggregation and heritability of sarcoidosis: a Swedish nested case−control study

Abstract: Sarcoidosis is believed to be caused by both genetic and environmental risk factors, but the proportion of the susceptibility to sarcoidosis that is mediated by genetics remains unknown. We aimed to estimate the familial aggregation and heritability of sarcoidosis using a case-control-family study design and population-based Swedish registers.We identified 23 880 individuals with visits for sarcoidosis in the Swedish National Patient Register using International Classification of Diseases codes (1964‒2013). In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
35
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 59 publications
(45 citation statements)
references
References 34 publications
5
35
2
1
Order By: Relevance
“…Due to the lack of detailed clinical information in the NPR, it is likely that there was some misclassification of sarcoidosis. However, preliminary validation data suggest that the accuracy of our definition is high (positive predictive value >90%; unpublished data), and as we have shown previously [4,23], our results are robust to nondifferential misclassification of sarcoidosis. In addition, we observed an association in the Karolinska sarcoidosis cohort despite small numbers and differences in serious infection predictors at baseline (e.g.…”
Section: Discussionsupporting
confidence: 77%
“…Due to the lack of detailed clinical information in the NPR, it is likely that there was some misclassification of sarcoidosis. However, preliminary validation data suggest that the accuracy of our definition is high (positive predictive value >90%; unpublished data), and as we have shown previously [4,23], our results are robust to nondifferential misclassification of sarcoidosis. In addition, we observed an association in the Karolinska sarcoidosis cohort despite small numbers and differences in serious infection predictors at baseline (e.g.…”
Section: Discussionsupporting
confidence: 77%
“…Moreover, some misclassification of sarcoidosis is expected as we relied on ICD codes and results of histological examinations, bronchoscopies, or imaging were not available. As previously shown [3,27], even large misclassification is unlikely to alter our inferences. Furthermore, because phenotyping sarcoidosis using ICD codes may lead to misclassification, we could not assess whether infections at a site were associated with sarcoid manifestations at the same site.…”
Section: History Of Infectious Disease N (%)supporting
confidence: 53%
“…This disturbance leads to systemic granulomatous inflammation, which predominantly affects the pulmonary and lymphatic systems [2]. Infectious agents are perceived to be likely candidates for explaining the environmental fraction of disease etiology [2], which was estimated to be accountable for about 61% of the susceptibility to disease [3].…”
Section: Introductionmentioning
confidence: 99%
“…The ACCESS study (A Case Controlled Etiologic Sarcoidosis Study) demonstrated that first-degree relatives of patients with sarcoidosis have a five times higher relative risk of developing sarcoidosis than control subjects [151][152][153]. A more recent study (Swedish National Patient Register using International Classification of Diseases codes, 1964-2013) confirmed that having at least one first-degree relative with sarcoidosis is associated with a 3.7fold increase in the risk of sarcoidosis [154]. The relative risk increases in those with two or more relatives (relative risk 4.7) and in Löfgren's syndrome (relative risk 4.1).…”
Section: Familial Genetic Risk: Clinical Evaluationmentioning
confidence: 99%